Level of Elderly Depression in Palopo City - Amrin, Awaluddin; Cahaya, A.; Yusriadi, Yusriadi; Sakkir, Geminastiti (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2020)
Depression is a mental health problem. The number of elderly now increasing, so that the elderly with a variety of changes both biologically, socially, culturally, economically, healthy, and psychologically become a vulnerable group to a variety of mental and behavioral problems. Elderly in the City of Palopo. This type of research is a descriptive correlation analysis with a cross-sectional method approach. The researchers recommend that local governments and health workers pay attention to factors associated with elderly depression because it plays an essential role in the prevention and cure of depressed elderly.